Inducible Alterations of Glutathione Levels in Adult Dopaminergic Midbrain Neurons Result in Nigrostriatal Degeneration - Chinta, Shankar J. (J Neurosci, 2007)
Parkinson's disease is a neurodegenerative disorder characterized by the preferential loss of midbrain dopaminergic neurons in the substantia nigra (SN). One of the earliest detectable biochemical alterations that occurs in the Parkinsonian brain is a marked reduction in SN levels of total glutathione (glutathione plus glutathione disulfide), occurring before losses in mitochondrial complex I (CI) activity, striatal dopamine levels, or midbrain dopaminergic neurodegeneration associated with the disease. Previous in vitro data from our laboratory has suggested that prolonged depletion of dopaminergic glutathione results in selective impairment of mitochondrial complex I activity through a reversible thiol oxidation event. To address the effects of depletion in dopaminergic glutathione levels in vivo on the nigrostriatal system, we created genetically engineered transgenic mouse lines in which expression of γ-glutamyl cysteine ligase, the rate-limiting enzyme in de novo glutathione synthesis, can be inducibly downregulated in catecholaminergic neurons, including those of the SN. A novel method for isolation of purified dopaminergic striatal synaptosomes was used to study the impact of dopaminergic glutathione depletion on mitochondrial events demonstrated previously to occur in vitro as a consequence of this alteration. Dopaminergic glutathione depletion was found to result in a selective reversible thiol-oxidation-dependent mitochondrial complex I inhibition, followed by an age-related nigrostriatal neurodegeneration. This suggests that depletion in glutathione within dopaminergic SN neurons has a direct impact on mitochondrial complex I activity via increased nitric oxide-related thiol oxidation and age-related dopaminergic SN cell loss.